2022
DOI: 10.3389/fmats.2022.953759
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermal, and structural investigations of chemically strengthened Na2O–CaO–Al2O3–SiO2 glasses

Abstract: For a series of conventional soda-lime-silicate glasses with increasing Al2O3 content, we investigated the thermal, mechanical, and structural properties before and after K+-for-Na+ ion-exchange strengthening by exposure to molten KNO3. The Al-for-Si replacement resulted in increased glass network polymerization and lowered compactness. The glass transition temperature (Tg), hardness (H) and reduced elastic modulus (Er), of the pristine glasses enhanced monotonically for increasing Al2O3 content. H and Er incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 108 publications
2
7
0
Order By: Relevance
“…Overall, the magnitude of CS is consistent with the results from an earlier study using the same glass 27 . For comparison, notable larger surface compression on the order of ∼500 MPa is commonly realized in standard soda–lime silicate glasses, 4 whereas Na + /K + ‐ion exchange enables permanent surface compressive stress up to ∼1 GPa in sodium‐aluminosilicate glasses 15–17 . This large variability among different glasses can be explained at least partially by variations in the alkali oxide concentrations, in particular the amount of K + ions present in each glass before ion exchange.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Overall, the magnitude of CS is consistent with the results from an earlier study using the same glass 27 . For comparison, notable larger surface compression on the order of ∼500 MPa is commonly realized in standard soda–lime silicate glasses, 4 whereas Na + /K + ‐ion exchange enables permanent surface compressive stress up to ∼1 GPa in sodium‐aluminosilicate glasses 15–17 . This large variability among different glasses can be explained at least partially by variations in the alkali oxide concentrations, in particular the amount of K + ions present in each glass before ion exchange.…”
Section: Resultssupporting
confidence: 87%
“…To effectively prevent the generation of defects during glass processing or handling, surface compressive layers extending to depths greater than 50 µm are required 2,10,11 . The implementation of Al 2 O 3 was found to significantly improve the interdiffusion of alkali cations inside the glass, 4,12–14 leading to layer depths on the order of 10 2 µm along with the creation of very high levels of surface compressive stress up to ∼1 GPa 15–17 . This points out the central role of an optimized glass composition and adapted network topology for the efficiency of the ion exchange process 18 .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…[6][7][8][9] Many studies have been reported on enhancing the mechanical strength of CAS glass frit through chemical strengthening or crystallization. [10][11][12] Chemical strengthening involves an ion exchange process that takes place within a molten salt bath. During this process, previously contained alkali ions in glass composition, such as Na + , are exchanged with larger ions like K + , leading to the formation of compressive stress on the surface.…”
Section: Introductionmentioning
confidence: 99%